Kesenjangan Antara Sistem Pendidikan Dan Kebutuhan Keterampilan Digital Industri Dalam Mendukung Transformasi Digital Nasional - Sarah Sagita (Jurnal Ilmu Administrasi dan Studi Kebijakan (JIASK), 2026)
National digital transformation has shown upward trend, however, the readiness of workforce with future-ready digital skills remains constrained by persistent gaps. This study aims to analyse the root causes of misalignment between education system and digital skill demands of industry in supporting Indonesia’s national digital transformation. The research employs a policy analysis approach using conceptual frameworks of future-ready digital skills and demand-driven skills development, alongside Bardach’s policy alternative evaluation method to assess the effectiveness of existing policy design. The findings indicate that the core problem does not lie in the absence of programmes, but rather in the lack of a binding and cross-sectoral national mechanism to systematically and sustainably translate industry digital skill demands into curriculum reform, workforce training, and certification systems. Policy fragmentation has led to sectoral interventions with limited impact on structural changes in provision of digital talent. This study recommends the establishment of national regulatory mechanism to integrate digital occupational competency standards into formal education system as a means to strengthen governance in digital skills alignment. The findings contribute to public policy development in the field of digital human resource development by emphasising the importance of integrated and adaptive regulatory design in response to dynamic industrial change